Psychology's compositional problem - Hillner, Kenneth P. (Advances in psychology (Amsterdam, Netherlands), 1987)
The primary purpose of this book is to document the pervasive ramifications of the compositional problem (the discipline's historical inability to define or give a technical specification to psychological phenomena) for the conduction of academic, experimental psychology at five levels of analysis: methodological, epiphenomenal, explanatory, metaphysical, and normative.